Survival Is for the Fittest : Export Survival Patterns in Georgia - Martuscelli, Antonio; Varela, Gonzalo (World Bank Group, Washington, DC, 2015)
This paper analyzes the determinants of export flow survival in Georgia. The paper uses a unique Georgian firm-level data set, in which firms' characteristics and output dynamics are matched with their customs' export transactions, for the period 2006-12. A discrete survival model is used to explore the role of firm level characteristics, diversification strategies, and network effects on the survival rates of export flows. Low survival rates at the product level are found to limit the ability of Georgian firms to consolidate new products in international markets. The analysis finds that it is production efficiency, rather than size, that boosts export survival chances, that firms diversification strategies matter for the prospects of survival, and that there is strong evidence of network effects in export survival. The analysis also finds that ratified foreign trade agreements contribute to increase the survival of export flows by reducing policy-induced trading costs and increasing information about destination markets.